Impact of Psychological Distress on Success of Information Technology Projects in Pakistan: The Role of Work Engagement - Zainish Aslam; Dr. Shahid Iqbal; Dr. Ehtasham Ul Haq (Social Science Review Archives, 2025)
This study focuses on success of IT projects in Pakistan because of the significant impact that it has on helping Pakistan gain its competitive edge in the world. By considering the social-cultural side of IT projects and its impact on project success this study focuses on understanding the indirect relationship between psychological distress and project success with work engagement playing the role of a mediator and leader-member exchange playing the role of moderator between psychological distress and work engagement to increase project success ratio. Using snowball sampling, data was collected from 181 respondents across Pakistan. Our findings suggested that work engagement does play the role of mediator as it has a negative relationship with psychological distress but a positive relation with project success and that in IT industry of Pakistan leader-member exchange doesn’t moderates the negative impact of psychological distress on work engagement.